Contracting under asymmetric information: Evidence from lockup agreements in seasoned equity offerings - Karpoff, Jonathan M.; Lee, Gemma; Masulis, Ronald W. (Journal of Financial Economics, 2013)
We document the frequent use of lockup agreements in seasoned equity offerings (SEOs) and examine the determinants of their use, duration, and early release. We find that the likelihood of an SEO lockup and its duration are positively related to issuer information asymmetry measures. Lockup duration is negatively related to underwriter spreads and underpricing, indicating that lockups lower expected flotation costs. Lockups are frequently released early following share prices rises. We conclude that lockups represent a contracting solution to asymmetric information and agency problems that plague equity issues by helping to insure SEO quality and deter opportunistic insider trading.